Resource Misallocation in India : The Role of Cross-State Labor Market Reform - Mohommad, Adil (IMF Working Papers; Working Paper, 2021)
At the macro level, productivity is driven by technology and the efficiency of resource allocation, as outcomes of firms' decision making. The relatively high level of resource misallocation in India's formal manufacturing sector is well documented. We build on this research to further investigate the drivers of misallocation, exploiting micro-level variation across Indian states. We find that states with less rigid labor markets have lesser misallocation. We also examine the interaction of labor market rigidities with informality which is a key feature of India's labor markets. Our results suggest that reducing labor market rigidities in states with high informality has a net positive effect on aggregate productivity.